Subjectivity and the labour process : a case study in the restaurant industry - Sosteric, Mike [Verfasser] (My University, 1996)
"This study focuses on the work experiences of employees, and on the changing relationships between employees and managers, in a mid- sized popular dance nightclub in a small western Canadian city. This nightclub had, in many ways, a unique organisational environment. Normative expectations about the quality of work in the food and beverage industry (de-skilled, highly standardised) did not initially hold. Employees developed an articulate and sophisticated culture that placed much of the training and decision-making responsibility squarely on their hands. However, internal and external pressures on management prompted the shift from a form of organising the workplace that could have been characterised as responsible autonomy to a more direct and autocratic form of control. This shift had the effect of destroying the organisational culture and stripping the employees of much of their responsibility for employee socialisation and customer service. The impact of these management initiatives on the employees, clientele and 'buttom line' of the nightclub is the major concern of this paper." (author's abstract, IAB-Doku) ((en)) Die qualitative Studie befasst sich mit den Arbeitsbedingungen und dem Verhältnis von Angestellten und Management in einem kanadischen Nachtklub. Die Arbeitssituation dort war ursprünglich von grosser Eigenverantwortung des Servicepersonals bestimmt. Der Kundenkontakt war durch die persönlichen Eigenarten und Eigenmächtigkeiten der Bedienungen geprägt. Untersucht werden die Bemühungen des Managements die Autonomie der Angestellten zu unterbinden und die Art der Arbeitsausübung zu vereinheitlichen und zu kontrollieren. (IAB)
Keywords: G 1.2.4.2.3 Gastgewerbe; G 2.3.1 Arbeitsteilung & -organisation; G 2.4.4 Biografiegestaltung; T 4.2 Psychologie; I 2.3.2 Nordamerika; Gastgewerbe; Arbeitsbedingungen; Tätigkeitsmerkmal; Persönlichkeit; Gästebetreuer; Berufsproblem; Kontrolle; Personalentwicklung; Kanada; 1989-1992